Eggshell membrane: Review and impact on engineering. (November 2016) - Park, Sunho; Choi, Kyoung Soon; Lee, Dohyeon; Kim, Daun; Lim, Ki Taek; Lee, Kyeong-Hwan; Seonwoo, Hoon; Kim, Jangho
Abstract : Agricultural bioresources are being recognised as emerging functional platforms that can find application in biological, environmental, and agricultural engineering. Eggshell membrane (ESM), the protein-rich membrane between the eggshell and egg white, has usually been regarded as waste and overlooked. However, its potential is now being highlighted in many engineering fields. This review provides basic information about ESM starting with its structural, chemical, and physical properties, and expands on its role in engineering fields. It touches upon various fabrication methods for constructing compatible ESM-based functional platforms. The review focuses on the role and performance of ESM in engineering applications: electric devices, sensors, environmental engineering, biomedical engineering, and commercialization. Finally, new perspectives about the potential of ESM as a highly valuable bioresource in various engineering fields are discussed. Highlights: Eggshell membrane (ESM) is recognised as emerging functional engineering platforms. Basic information on ESM and its contribution engineering fields are described. Fabrication methods for compatible ESM-based functional platforms are discussed. New potentials for ESM are proposed as highly valuable engineering platforms.